Contract with a Chinese Face: Socially Embedded Factors in the Transformation from Hierarchy to Market, 1978-1989 - Cheng, Lucie; Rosett, Arthur (Columbia Journal of Asian Law, 1991)
This article examines how contract law came to play an important new role in the organization of the Chinese economy during the decade of reform in the People’s Republic of China (“PRC’), 1978- 1989. Crucial to the movement for reform was the effort to create new institutions to expand, regulate, and channel economic transactions. These institutions were designed to complement centralized planning as the basic means of allocating goods and services. They emphasized limitation and decentralization of planning decisions, the creation of economic incentives, and the increased responsibility of economic actors for the consequences of their actions. These new institutions were introduced in response to a variety of organizational problems in agriculture, industry, and commerce. Nonetheless, they shared common features: the responses in all cases emphasized notions of contract, the legal responsibility of economic actors to perform their agreements, and the value of individual autonomy in setting the terms of economic transactions and relationships.